2019
DOI: 10.1515/chem-2019-0102
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production by Lipids From Indonesian strain of Microalgae Chlorella vulgaris

Abstract: The fatty acid methyl ester (FAME) production from Chlorella vulgaris has been studied by sequential investigation such as microalgae culturing, lipid extraction, and lipid conversion to FAME. The C. vulgaris could grow well in the BG-11 medium and had a doubling time 3.7 days for its growth using inocula 16% (v/v). The optimum of dry cell biomass as 11.6 g/L was obtained after the microalgae culture harvested for 6 days. Lipid extraction from the biomass was carried out in various solvents and ultrasonication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…RRSE2. These observations are in agreement with an earlier report, which stated that the presence of 12% linolenic acid is acceptable for the quality biodiesel (Arroussi et al 2017;Purkan et al 2019). It has been reported that the components such as palmitic, oleic, stearic, linoleic and linolenic acid were considered as the most common fatty acids in biodiesel by Knothe (2008).…”
Section: The Fatty Acid Profile Of Nitzschia Sp Rrse2 Cultivated In Optimized F/2 Mediumsupporting
confidence: 93%
“…RRSE2. These observations are in agreement with an earlier report, which stated that the presence of 12% linolenic acid is acceptable for the quality biodiesel (Arroussi et al 2017;Purkan et al 2019). It has been reported that the components such as palmitic, oleic, stearic, linoleic and linolenic acid were considered as the most common fatty acids in biodiesel by Knothe (2008).…”
Section: The Fatty Acid Profile Of Nitzschia Sp Rrse2 Cultivated In Optimized F/2 Mediumsupporting
confidence: 93%
“…that are usually known as nonrenewable sources of energy. The acceptability of the green alga, Chlorella vulgaris, as a potential biofuel feedstock is found worldwide, as mentioned by Ru et al (2020), Varaprasad et al (2020), Purkan et al (2019), Ramírez-López et al (2019, Sakarika and Kornaros (2019), Papapolymerou et al (2018), Suthar and Verma (2018), Daliry et al, (2017), Lam et al (2017), Rajanren and Ismail (2016), Villagracia et al (2016), El-Sayed et al (2015), Safi et al (2014), Jasim and Maysam (2014), Mallick et al (2011), Phukan et al (2011, though the amount of biomass produced can vary due to the production scale, operational design, and optimum growth conditions taken under consideration.…”
Section: Production Of Chlamydomonas Noctigama Chlorella Vulgaris Anabaena Variabilis Andmentioning
confidence: 99%
“…Dilihat dari potensinya, perairan Indonesia sangat cocok untuk pengembangan dan budidaya mikroalga. Mikroalga Chlorella vulgaris dan Spirulina platensis merupakan jenis mikroalga yang banyak ditemukan di perairan Indonesia, namun budidaya secara masif dan dalam skala ekonomis belum dilakukan (Purkan et al 2019). Alasan pasti belum berkembangnya budidaya Chlorella vulgaris dan Spirulina platensis secara komersial di Indonesia tidak diketahui secara detail, namun permasalahan terkait tingginya biaya investasi dan terbatasnya penguasaaan teknologi merupakan faktor yang dapat menjadi kendala pengembangan kedua mikroalga tersebut di Indonesia.…”
Section: Peluang Pengembangan Dan Pemanfaatan Chlorella Vulgaris Dan unclassified